Electrical imaging techniques for groundwater pollution studies: a case study from tamil nadu state, south india (2009)
An attempt was made to identify the extent of pollution in the aquifer matrix of Tirupur, a highly industrialized zone of Tamilnadu state, South India. Electrical imaging techniques were adopted with a Syscal Pro-96 system, for measuring apparent resistivity values using different electrodes separation. The first profile conducted atValipalayam recorded a resistivity range of 45.5 Ùmwas observed at a depth of 27 to 47 mindicating the possibility of contamination. The second profile conducted at Pethichettipuram indicates source of contaminationat left end corner with a drop in resistivity